Les espaces politiques des substances chimiques - Brice Laurent (Revue d'anthropologie des connaissances)
This paper focuses on the operations that define chemicals. It discusses the case of nanomaterials, which is a situation where the uncertainty about the very existence of objects is uncertain. By describing controversies related to definition criteria and the modalities of collective discussion, the paper highlights the interest of analysing the empirical sites where ontological uncertainty is dealt with for the study of political spaces. The paper describes an international space characterized by the importance of the separation between scientific expertise and national policy decisions; a European space where the oppositions about the definition of “nano” categories engage the principles underlying the European public action; and, eventually, a national space, in France, where experiments are conducted for uncertain results.